Koreografi Tari Piring Di Ateh Karambie Di Kanagarian Payo Kelurahan Tanah Garam Kecamatan Lubuk Sikarah Kota Solok - Maharani Maharani; Herlinda Mansyur (SENDRATASIK UNP, 2020)
This study aims to reveal and describe the choreography of a dance called Tari Piring Diateh Karambie in Kanagarian Payo, Tanah Garam Village, Lubuk Sikarah District, Solok City. This research is a qualitative research using descriptive method. The main instrument of this research was the researcher itself and was assisted by supporting instruments such as writing instruments and voice recorders. This research used primary and secondary data. The data were through literature study, observation, interviews, and documentation. The data analysis was conducted by collecting the data, reducing the data, presentation the data, and making conclusions. The results show that Tari Piring Diateh Karambie a is a traditional dance using a choreographic approach, and it is cultivated by raising the life of nature and the people of Nagari Payo. This dance has been around since 1995. Tari Piring Diateh Karambie uses elements of dance composition consisting of: 7 types of movement, simple floor pattern, top design, music, dramatic design, dynamic, theme, composition, group, and equipment. The movement of Tari Piring Diateh Karambie comes from a combination of Nagari Payo and Simawang. The movements and floor patterns used by dancers have fulfilled the elements of the dance composition. There is also music to accompany the dance movement so that it makes the dance alive as well as it complements the dance. The equipment used also gives the nuance to the dance so that it is not monotonous. In addition, the group choreography shows high social values and depicts the nature around Nagari Payo